An Analysis of Ibn Taimmiyah's Hijā' in Qasīdah Lāmiyah as the Identity of the Mahdzab Hambali - Fauzi, Abi; Liza, Fitri (Universitas Muhammadiyah Sumatera Barat, 2024)
This research aims to analyze the style of satire (hijā’) used by Ibn Taymiyyah in his book titled